Estudos moleculares, estruturais e funcionais da Cel12A de Gloeophyllum trabeum, uma endo-1,4-β-glucanase da família 12 de hidrolases de glicosídeos - Miotto, Lis Schwartz (Universidade Federal de São Carlos, 2014)
The production of second-generation ethanol by enzymatic hydrolysis of biomass is considered a viable and promising alternative to face the global energy crisis and to decrease our dependence on fossil fuels. Therefore, it is necessary to degrade the constituent molecules of the plant cell wall such as lignin, cellulose and hemicellulose to fermentable sugars. However, the use of enzymes for this purpose is still expensive, leading to the increase on studies seeking to make them more feasible economically and technically. The present study aimed the molecular, structural and functional characterization of the endoglucanase Cel12A from the fungus Gloeophyllum trabeum by different techniques. Biochemical data revealed the substrate specificity for the enzyme and showed that β-glucan is the best substrate for its activity (239.2 ± 9.1 U mg-1). Optimal conditions for activity were pH 4.5 and temperature of 50 oC. Thermal stability assay indicated a half-life of 84.6 ± 3.6 hours at 50 oC. The kinetic parameters Km (3.2 ± 0.5 mg mL-1) and Vmax (0,40 ± 0,02 μmol min-1) were determined using β-glucan as substrate. Analysis of scanning electron microscopy of oat spelts and filter paper samples submitted to the hydrolysis by GtCel12A evidenced the degradation effects of these substrates compared to control samples. Moreover, the low-resolution envelope and the crystallographic structure for GtCel12A were determined. The structure revealed a β-sandwich fold with two β-sheets (A and B) and three α-helices, while sheet A showed five strands and sheet B nine strands. The comparative analysis of the amino acid sequence and homologous structures prompted us to identify the catalytic residues, Glu142 and Glu227 in the active site of the enzyme. These results are important for understanding and elucidating the enzyme molecular mechanism of action and other glycoside hydrolase family 12 endoglucanases.
Molecular, structural and functional studies of the Cel12A from Gloeophyllum trabeum, an endo-1,4-β-glucanase from the family 12 of glycosyde hidrolases
Keywords: Bioquímica; Celulase; Endoglucanase; Biofísica; Cristalografia de raio X; Cellulase; Endoglucanase; Biochemistry; Biophysics; X-ray crystallography; OUTROS